(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
A new phenomenon in the field of linguistics is envisioned as a result of the advent of social media among youth, and the article fathomed the research on linguistics’ problems after social media’s advent.